Thermal performance evaluation of isolation and two active solar heating systems for an experimental module: A rural Peruvian case at 3700 masl - Molina J.O. (2019)
Evaluation results of the thermal performance of an experimental housing module (EHM) are presented with considerations for the level of insulation and the installation of two active heaters powered by solar energy. The EHM is located in a high Andean rural area in southern Peru (latitude: 13° 45'40" S, longitude: 73° 51'26" W, and elevation: 3700 masl), where in situ measurements were made. The design and implementation of the EHM was based on the application of bioclimatic strategies and techniques. For the thermal evaluation of the EHM, 43 temperature sensors connected to dataloggers were used. The results show that the temperature inside the EHM increased more than 12 °C with respect to the outside temperature in the critical hours of extreme cold and frost when the isolation and the proposed radiative systems are used. Finally, the thermal behavior of the EHM was simulated using the EnergyPlus 8.4 program, which showed that there was an average difference of 0.5 °C between the measured interior temperature and the corresponding simulated temperature.